If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -2t = 14 + t Solving 8 + -2t = 14 + t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. 8 + -2t + -1t = 14 + t + -1t Combine like terms: -2t + -1t = -3t 8 + -3t = 14 + t + -1t Combine like terms: t + -1t = 0 8 + -3t = 14 + 0 8 + -3t = 14 Add '-8' to each side of the equation. 8 + -8 + -3t = 14 + -8 Combine like terms: 8 + -8 = 0 0 + -3t = 14 + -8 -3t = 14 + -8 Combine like terms: 14 + -8 = 6 -3t = 6 Divide each side by '-3'. t = -2 Simplifying t = -2
| 2(2y-1)+y=5(y+3) | | -9x+5(-3x-4)=-42-2x | | 40+40*0+1= | | 2x+7(3x-4)=-2-3x | | -8x^2+24x-18= | | -16+x=450 | | 5x^2+50x=0 | | -5x+x=-16 | | 120x^2-272x+120=0 | | 5*5*5*5= | | 2t^2+2t=3 | | 10-3(-8-2)= | | 120x^2-272x+102=0 | | 10x-0.375-4x=6x | | 2+x=16-6x | | 30a=2a-8 | | 976x-x^2=213.495 | | 1/14=27/7*1/30 | | 10x-2y=5 | | -2x^2+17x-8=0 | | 6x-2y=1 | | -99=33y | | 8j-4k=4 | | 5(k-2)-6=5k-(4k-3) | | 3j+4k=23.5 | | 11f+10g=25 | | Y=150x+800 | | 22=-2+3s | | -2-19= | | 4m(4n-8)+6mn-2m= | | -39(11x)+26(24x)= | | 3r-6t=15 |